Abnormalities of cortical excitability and cortical inhibition in cervical dystonia Evidence from somatosensory evoked potentials and paired transcranial magnetic stimulation recordings - Kanovský, Petr; Bares, Martin; Streitová, Hana; Klajblová, Hana; Daniel, Pavel; Rektor, Ivan (Journal of neurology, 2003)
Cortical excitability and cortico-cortical inhibition were examined in twenty-one patients suffering from idiopathic rotational cervical dystonia. Polymyography of cervical muscles, somatosensory evoked potential recordings, and paired transcranial magnetic stimulation were used to assess the dystonic disorder. The results were compared with those obtained in a group of sixteen healthy age-matched volunteers. Statistically significant differences between the patient group and the control group were found when the amplitude values of the mean P22/N30 component measured at F [3, 4] and C[3, 4]' electrode positions were compared. The mean amplitude of P22/N30 in both of these electrode positions contralaterally to the direction of head deviation was significantly higher in the patient group (p <or= 0.05). The mean side-to-side P22/N30 amplitude ratio was calculated in both groups in the F[3, 4] and C[3, 4]' electrode positions: there was a significant difference between the two groups. The mean ratio (calculated contralaterally/ipsilaterally in the patient group and left/right side in the control group) was significantly higher in the patient group (p <or= 0.05). There were statistically significant differences between the two groups when the mean values of MEP amplitudes following paired stimuli at short and medium interstimulus intervals (ISI)) were compared. The percentage of amplitude reduction registered at short ISI was significantly lower in the patient group when both 3 ms ISI and 5 ms ISI were considered, and when the hemisphere contralateral to the direction of head deviation was stimulated. There was also a difference (with the short ISI) when the hemisphere ipsilateral to the direction of head deviation was stimulated, but this difference was not significant (p < 0.5). Almost all of the amplitude changes following the paired stimulus at the longer ISI, i. e. 10, 15, and 20 ms were significantly different when the patient group was compared with control group: when the ipsilateral hemisphere was stimulated, the amplitude of conditioned responses was significantly higher following all three paired stimuli (with 10, 15, and 20 ms ISI) at the p <or= 0.05 significance level; when the contralateral hemisphere was stimulated, they were significantly higher following the 10 and 20 ms ISI paired stimuli (significance level p <or= 0.05). The interhemispheric difference in the patient group was significant only for the paired stimuli using 3 and 5 ms (short) ISI and 15 and 20 ms (medium) ISI. There was a significantly decreased inhibition at 3 and 5 ms ISI when the hemisphere contralateral to the direction of head deviation was stimulated, as compared with the hemisphere ipsilateral (p <or= 0.05). Similarly, there was a significantly increased facilitation at 15 and 20 ms when the hemisphere contralateral to the direction of head deviation was stimulated, as compared with the hemisphere ipsilateral (p <or= 0.05). The results indicate that a disorder of both cortical excitability and intracortical inhibition exists in patients with cervical dystonia, and that this disorder is lateralized, i. e. it is located within the hemisphere contralateral to the direction of head deviation.
Keywords: Male; tortikolis; transkraniální magnetická stimulace; Transcranial Magnetic Stimulation; Physical Stimulation; nervový útlum; mozková kůra; Adult; Muscle, Skeletal; dospělí; mužské pohlaví; fyzikální stimulace; Median Nerve; Neural Inhibition; kosterní svaly; lidé; ženské pohlaví; Humans; nervus medianus; Torticollis; somatosenzorické evokované potenciály; Evoked Potentials, Somatosensory; Female; lidé středního věku; Middle Aged; Cerebral Cortex